Development of Physics E-Learning Based on Discovery Learning to Improve Students' Conceptual Understanding and Learning Interest - Pratiwi, Juli; Rahmad, M.; Syahril, Syahril (JTP - Jurnal Teknologi Pendidikan, 2024)
Thermodynamics material is abstract material that causes misconceptions. Misconceptions are caused by several things, one of which is the use of learning media that has not been maximized. The procedure for developing physics e-learning based on discovery learning uses the ADDIE type Instructional Design and only reaches the practicality test stage. The developed e-learning contains attendance, discussion forums, e-modules that guide students to improve their understanding of concepts, learning videos, power points, student worksheets, quizzes, summative assessments, glossaries and references to other relevant reading sources with a validity value of 0.92 with a very valid category, a teacher's practicality value of 95.00 and a student's practicality value of 90.25 with a very practical category. Based on the results of validity and practicality, it can be concluded that physics e-learning based on discovery learning is feasible to use in physics learning.